Efeito da altura do dossel e da época do ano sobre as características agronômicas e nutricionais do capim-elefante fresco e ensilado - Alves, Eveline Bueno (2017)
Elephant grass is an important source of fodder in many countries, however, its dynamics of growth, in cut-and-carry systems, is not yet known. The objective of this study was to determine the forage accumulation rates and morphological componentes accumulation rate, and the growth dynamics of elephantgrass (Pennisetum purpureumSchum. Cv Cameroon) incut-and-carry systems. The evaluated canopy heights were: 1.00, 1.40, 1.80, 2.20 and 2.60 m. The experiment was carried out in 25 plots of 28.8 m² each with six rows of 6 meters. The experimental period occurred from November 2014 to November 2016, two rainy seasons (summer, from 11/01 to 03/21) and two dry seasons (winter, from 03/22 to 10/31) in the two years. The fertilization consisted of 400 kg of N, 200 kg of K2O and 60 kg of P2O5per hectare per year, performed every 15 days. These plants were weighed, the tillers were counted and the forage was separated into leaves, stems and dead material. Linear (LIN) and quadratic (QUA) models were tested using PROC REG and exponential (EXP), linear with plateau (LCP) and sigmoid (SIG) models were tested by PROC NLIN from SAS. The Akaike information criterion was used to select the best model. With the results of this thesis it was possible to identify key points on the growth dynamics of Elephant grass cultivated in cut-and-carry systems. Elephant grass can be managed up to 1.40 m without any prejudice in fiber digestibility. During the winter the elephant grass can be used, but it is necessary to consider the requirements of the animals to balance the diet due to the low digestibility of the grass. As for elephant grass silage, although silages prepared with plants harvested at lower altitudes have more digestible fibers, the losses from effluent are very high. Consider the production of digestible dry matter of silage produced per hectare to determine the management of the canopy, since there were no differences between the fermentation profile of the silages in this study.